A hybrid tabu-simulated annealing heuristic algorithm for optimum design of steel frames - Degertekin, S. O.; Hayalioglu, M. S.; Ulker, M. (Techno-Press, 2008)
A hybrid tabu-simulated annealing algorithm is proposed for the optimum design of steel frames. The special character of the hybrid algorithm is that it exploits both tabu search and simulated annealing algorithms simultaneously to obtain near optimum. The objective of optimum design problem is to minimize the weight of steel frames under the actual design constraints of AISC-LRFD specification. The performance and reliability of the hybrid algorithm were compared with other algorithms such as tabu search, simulated annealing and genetic algorithm using benchmark examples. The comparisons showed that the hybrid algorithm results in lighter structures for the presented examples.
Keywords: optimum design; steel frames; tabu search; simulated annealing; hybrid heuristic algorithm